Retapamulin Activity Against Pediatric Strains of Mupirocin-resistant Methicillin-resistant Staphylococcus aureus. Issue 7 (July 2021) - Patel, Ami B.; Lighter, Jennifer; Fulmer, Yi; Copin, Richard; Ratner, Adam J.; Shopsin, Bo
Abstract : Retapamulin activity against 53 isolates obtained from a mupirocin-resistant community-acquired methicillin-resistant Staphylococcus aureus pediatric disease cluster was evaluated using broth microdilution. All strains were susceptible to retapamulin with minimum inhibitory concentrations ⩽ 0.5 μg/mL. DNA sequence analysis of rplC and cfr identified one rplC strain variant that did not demonstrate reduced phenotypic susceptibility to retapamulin. These results demonstrate that retapamulin may be a useful alternative therapy for mupirocin-resistant community-acquired methicillin-resistant S. aureus, especially in disease clusters.